1999
DOI: 10.1007/s004280050329
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant positioning of trophoblast and lymphocytes in the feto-maternal interface with pre-eclampsia

Abstract: Pregnancy represents the growth of an allograft where fetal trophoblast cells evade immune rejection and invade maternal tissue. There should be a balance between fetal trophoblast and maternal immune-responsive cells and alterations in the proportion of these cells may relate to pregnancy disorders. To test this, the decidual tissue of placental bed biopsies was examined and trophoblast cells and lymphocytes were quantified morphometrically; spiral arteries were classified as unchanged, transformed or affecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
5
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 14 publications
3
57
5
1
Order By: Relevance
“…However, the findings contrast with those of Stallmach et al (1999) and Bachmayer et al (2006) who reported increased numbers of CD56C cells in PE decidua compared with controls. In the absence of information on the FGR status of the PE study groups in these latter studies, use of placental bed biopsy and the avidinbiotin method, which is more sensitive than the PAP method used by Stallmach et al (1999), may also partly account for the differences in uNK cell numbers.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, the findings contrast with those of Stallmach et al (1999) and Bachmayer et al (2006) who reported increased numbers of CD56C cells in PE decidua compared with controls. In the absence of information on the FGR status of the PE study groups in these latter studies, use of placental bed biopsy and the avidinbiotin method, which is more sensitive than the PAP method used by Stallmach et al (1999), may also partly account for the differences in uNK cell numbers.…”
Section: Discussioncontrasting
confidence: 99%
“…Studies of human decidual leucocyte populations in PE and FGR are limited. Khong (1987) reported no differences in placental bed and non-placental bed leucocyte populations in PE compared with normal-term pregnant controls while Stallmach et al (1999) reported an increase in CD8CT cells and CD56C uNK cells in decidua from women with PE. These observations were confirmed in a flow cytometric study, CD56C cells also showing an altered phenotype with a shift from the CD16KCD56C to the more cytotoxic CD16CCD56C phenotype (Wilczynski et al 2003).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Increased numbers of CD4+ T lymphocytes have been reported in decidua from women with pre-eclampsia compared to age matched controls (Stallmach et al, 1999;Wilczynski et al, 2003). However, work in our laboratory demonstrated a reduction in both CD3+ and CD8+ cells in pre-eclampsia (Scaife, Innes, Searle, Robson, Bulmer; unpublished data).…”
Section: T Lymphoctyes In Pathological Pregnancymentioning
confidence: 68%
“…Preeclampsia, and the related fetal growth restriction, are interpreted as consequences of impaired trophoblast invasion (1,6). Severe reduction of trophoblast cells, in combination with a strong increase of maternal lymphocytes and dNK cells, is found in intrauterine growth restriction (7).…”
mentioning
confidence: 99%